2014
DOI: 10.1016/j.mgene.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Calpain 10 (rs2975760) gene polymorphism in Asian Indians with Gestational Diabetes Mellitus

Abstract: BackgroundType 2 Diabetes Mellitus (T2DM) and Gestational Diabetes Mellitus (GDM) are part of a heterogeneous and complex metabolic group of disorders that share common pathophysiological circumstances, including β-cell dysfunction and insulin resistance. The protein Calpain 10 (CAPN10) plays a role in glucose metabolism, pancreatic β-cell insulin secretion, and thermogenesis.ObjectivePolymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR–RFLP) based genotyping of CAPN10 (rs2975760) polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…However, there is no consensus on molecular diagnosis and screening in identification of diabetes patients. Current diagnosis and screening are based on biochemical analysis of coagulated blood serum (4). The results of the present study reveal that there is an association between TCF7L2 and SLC30A8 gene polymorphisms in PTDM in Asian Indians.…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Amentioning
confidence: 53%
See 1 more Smart Citation
“…However, there is no consensus on molecular diagnosis and screening in identification of diabetes patients. Current diagnosis and screening are based on biochemical analysis of coagulated blood serum (4). The results of the present study reveal that there is an association between TCF7L2 and SLC30A8 gene polymorphisms in PTDM in Asian Indians.…”
Section: Distribution Between Calcineurin Inhibitors Dosage In Ptdm Amentioning
confidence: 53%
“…Both PTDM and type 2 diabetes mellitus (T2DM) are multifactorial metabolic disorders (3). T2DM is a chronic disease, characterized by insulin resistance and impaired insulin secretion from pancreatic β-cells (4). PTDM incidence has been increasing dramatically throughout the globe, in parallel to T2DM (5).…”
Section: Introductionmentioning
confidence: 99%
“…The selection of T2DM subjects, controls, and PTDM subjects and the inclusion and exclusion criteria for the specific groups are described in previous publications (1,5,11). We collected 3 mL of serum for biochemical analysis and 2 mL of anticoagulated blood for mutational analysis.…”
Section: Selection Of Subjectsmentioning
confidence: 99%
“…Impaired β-cell function and insulin resistance are key determinants of T2DM (1). The etiology of T2DM is thought to involve genetic and environmental factors, and the disease is characterized by decreased insulin secretion and insulin resistance (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, not all pregnant women exposed to certain risk factors go on to develop gestational diabetes mellitus, suggesting that hereditary factors may contribute to the occurrence of this disease. Currently, many epidemiologic studies have shown that certain genes, such as melatonin receptor type 1B (MTNR1B), lipoprotein lipase gene, potassium channel voltage gated KQT-like subfamily Q, member 1 (KCNQ1), methylenetetrahydrofolate reductase (MTHFR), factor V Leiden (FVL), and adiponectin gene and adenosine deaminase, contribute to the susceptibility to gestational diabetes mellitus (Khan et al, 2014;Ao et al, 2015;Li et al, 2015a;Takhshid et al, 2015a,b).…”
Section: Introductionmentioning
confidence: 99%